113 RIGHT VENTRICULAR FREE WALL LONGITUDINAL STRAIN AS THE SOLE MARKER OF RIGHT VENTRICLE SYSTOLIC DYSFUNCION IN HYPERTROPHIC CARDIOMYOPATHY: A CLINICAL CASE. (15th December 2022) - Stankowski, Kamil Mateusz; Figliozzi, Stefano; Cannata, Francesco; Fazzari, Fabio; Mantovani, Riccardo; Curzi, Mirko; Panico, Cristina; Catapano, Federica; Ceriotti, Carlo; Galimberti, Paola; Giuseppe Stefanini, Giulio; Frontera, Antonio; et al.
Abstract: Background: The introduction of Cardiac-MRI (cMRI) in clinical practice has considerably improved risk stratification of patients with hypertrophic cardiomyopathy (HCM). However, the prediction of adverse outcome based on imaging markers remains suboptimal. Right ventricular (RV) involvement is an emerging finding in this disease of unknown clinical value. The identification of accurate and sensible imaging markers to detect morpho-functional alterations of the RV is therefore essential to establish, in the future, any prognostic impact of RV involvement in HCM in order to improve risk stratification. RV free wall longitudinal strain (RV-FWLS) is a promising marker to unveil subclinical RV dysfunction despite normal conventional indices of RV systolic function; however, RV-FWLS has been scarcely explored in HCM patients. Case Summary: A 29-year-old man with sarcomeric HCM due to MYBPC3 mutation was referred to our Institution. Trans-Thoracic Echocardiography (TTE) showed left ventricular (LV) apical hypertrophy (27 mm) with an ace of spades morphology and mid-ventricular obstruction (peak gradient 38 mmHg). LV-EF was normal (62%) while LV global longitudinal strain was significantly impaired (-9.3% with a reverse apical sparing pattern). 2nd-degree diastolic dysfunction and left atrial enlargement (maximum volume: 42 ml/m 2 ) were observed. No LV apical aneurysm nor paradoxical diastolic flow at the apex were noted. RV hypertrophy was present (maximum thickness 8 mm) with normal conventional indices of RV systolic function: TAPSE 26 mm, S' TDI 12 cm/s, FAC 50%. In contrast, RV-FWLS was significantly reduced (–16%). cMRI confirmed normal bi-ventricular function in presence of left and right hypertrophy (maximum wall thickness 28 and 12 mm, respectively) and LV apical thinning. At tissue characterization, elevated native T1 and T2 values were evident in the apex (1071 +/- 45 ms and 54 +/- 6 ms, respectively) and a significant amount of patchy LGE was present in the mid-apical segments of the LV (28% of LV mass) and of the RV. After consideration of clinical and imaging data, an s-ICD for primary prevention was implanted. Discussion: The present case highlights known issues and poses new challenges in managing HCM patients. First, it confirms the central role of cMRI, demonstrating its unique capability to spot myocardial fibrosis, guiding our decision to implant an s-ICD in our patient. Second, it draws attention to RV involvement in HCM, an emerging finding in this condition. MYBPC3 mutation has been associated with RV hypertrophy. Both of these conditions, together with patchy RV-LGE, were found in our patient. Notably, RV-FWLS was the only RV systolic index to be impaired and might represent an early and more accurate marker of RV systolic dysfunction compared to other conventional indices, including RV-EF by cMRI. Future studies assessing the prognostic value of RV involvement, including RV-LGE and RV-FWLS, are needed in HCM patients to potentially refine risk stratification in this challenging population.